2020
DOI: 10.32598/jesm.12.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Hip Abductor Muscles Strengthening's Effect on Lower Extremity's Function of Runners With Illitotibial Syndrome

Abstract: Introduction: Iliotibial Band Syndrome (ITBS) is among the most common injuries in distance runners. Thus, the present study investigated the effect of a special strengthening exercise program for abductor’s muscles according to NSCA protocol, on pain reduction and lower extremity function improvement among elite distance runners with ITBS. Materials and Methods: The subjects of the present study were 32 elite distance runners who were randomly divided into two groups of control and experimental (n=16/group). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Research by Beers et al, (2008) [42] showed a significant difference in hip abductor strength between healthy and injured leg before intervention which was ameliorated after 6 weeks of abductor strengthening. Imeri and Gheitasi's (2020) [44] study on hip abductor strengthening resulted in a significant decrease in pain, improvement in lower extremity functionality after the intervention and 3 months follow-up. Research by McKay et al, (2020) [43] examined the effectiveness of 3 different exercise programs: stretching, conventional exercise and experimental strength training with the results showing a significant improvement in balance and lower extremity function ability in the A-stretch group, without, differences between the 3 groups.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Research by Beers et al, (2008) [42] showed a significant difference in hip abductor strength between healthy and injured leg before intervention which was ameliorated after 6 weeks of abductor strengthening. Imeri and Gheitasi's (2020) [44] study on hip abductor strengthening resulted in a significant decrease in pain, improvement in lower extremity functionality after the intervention and 3 months follow-up. Research by McKay et al, (2020) [43] examined the effectiveness of 3 different exercise programs: stretching, conventional exercise and experimental strength training with the results showing a significant improvement in balance and lower extremity function ability in the A-stretch group, without, differences between the 3 groups.…”
Section: Discussionmentioning
confidence: 92%
“…Imeri and Gheitasi's (2020) [44] quasi-experimental study examined the effectiveness of a hip abductor strengthening exercise program in reducing ITBS symptoms and improving lower limb function. A total of 32 elite distance runners with a positive Noble's test were randomly divided into 2 groups: the experimental (n=16) and the control group (n=16).…”
Section: Rehabilitationmentioning
confidence: 99%